Assessment of Patient Safety Culture at Intensive Care Units in Public Hospitals in Benghazi from The Health Care Professional`s Perspective - Eman Alaqeli; Ainas Altarhuni (AlQalam Journal of Medical and Applied Sciences, 2021)
Background: Patient Safety Culture (PSC) is a major parameter for the improvement of patient safety in the healthcare system and is considered a challenge for health professionals especially at ICUs due to the nature of their work. This study aimed to assess patient safety culture at intensive care units in public hospitals in Benghazi from a healthcare professional`s perspective. Method: This was a cross-sectional descriptive study, comprised 73 healthcare professionals working in ICUs. For data gathering, a Hospital Survey of Patient Safety Culture (HSOPSC) questionnaire was used. This questionnaire was designed by the Agency of Health Research and Quality (AHRQ) in 2004. Data analysis was performed by SPSS (version 21) using descriptive statistics. Result: The study reported 38.5% average score of patient safety culture at ICUs. Among dimensions of patient safety culture, the highest rate of positive response rate was observed in ''Teamwork within units'' (60.4%), whereas the lowest rate was for ''non-punitive response to error'' (21.06%). Concerning patient safety grades, most healthcare professionals were rated as "accept" or "very good" grades at their units, and 72.6% did not report any events in the previous year. Conclusions: The finding of this study indicated that patient safety culture was fragile in ICUs and required significant changes in various aspects of PSC in the included hospitals.